Optimal Planning of Energy Hubs Considering Renewable Energy Sources and Battery Energy Storage System - Thang, V. V; Ha, Thanhtung (International Journal of Sustainable Energy and Environmental Research, 2019)
In the context of multiple energy loads, the energy hub is introduced as a unit where multiple energy carriers can be converted, conditioned, and stored to enhance the energy efficiency of the system. Therefore, this study presents an optimal planning framework, which aims the selection the invested size and time of equipment based on minimizing the life cycle cost considering renewable energy sources (RES) and battery energy storage systems (BESS). The input energies considered include the electrical energy, natural gas, solar radiation and wind that are converted to supply for output energies consisting of electricity, cooling, and heating. The planning framework with the objective function which is minimizing the life cycle cost of the project consists of the investing and operating cost of equipment, cost for purchasing energy from market (electricity, natural gas), the emission taxes cost and the replacement cost or residual value of equipment at the end of the planning period. The constraints as balance energy types, the size limit of equipment integrated into model together with binary variables make a mixed integer nonlinear programming (MINLP) planning problem. The feasibility of the proposed model and the effectiveness of renewable energy sources and BESS in optimal planning of energy hubs are tested by an assumed energy hub with the high-level algebraic modeling software, general algebraic modeling system (GAMS).